Необхідність державного регулювання економіки - Яковенко, Р. В.; Yakovenko, R.; Кобець, М. О.; Kobets, M. (м. Ірпінь : Університет ДФС України, 2017)
У тезах визначено сутність і трансформацію функцій державного регулювання економіки на сучасному етапі. In the theses, the essence and transformation of the functions of state regulation of the economy are defined at the present stage.
The need for state regulation of the economy
Keywords: державне регулювання економіки; трансформаційні зміни; економічні відносини; конкуренція; розподіл; ресурси; state regulation of economy; transformational changes; economic relations; competition; distribution; resources